Формирование среднего класса в Польше: движущие силы и препятствия - Доманьский, Х. (Социология: теория, методы, маркетинг, 2006)
Development of middle class society may be taken to measure a degree of modernization of post-communist societies in transition to the market system. Using survey data from both Poland and international studies the author examines the main
impediments and driving forces on this route. First, he shows here that the main
candidates to the post-communist middle class are higher managers along with intellectuals and owners. Regarding the second question — pace of formation of the middle class patterns — the author argues that Poland systematically (although slowly)
moved forward on this route which results in modernisation of occupational structure,
increase of average consumption and income, and particularly — constant rise of
meritocratic rules of distribution of monetary rewards. The third measurement concerned the development of cultural and economic liberalism regarded as the middle class
orientations. According to the European Social Survey 2004/2005 data, post-communist societies prove to be still less liberal that Western countries. The “mentality lag”
displays also in ratings of occupational prestige in Poland where business and managerial positions are marked with lower evaluations than expected. In this point the
author argues that really changes in orientations of statistical citizens of postcommunist societies seem to be enforced by objective requirements faced in work and in
daytoday activity. Confronted with harsh reality of the market relations, emerging
middle class society is more enforced than willingly accepted.